Plasma apolipoprotein E and monocyte chemoattractant protein-1 levels in young people with HIV and ischemic stroke in Lusaka, Zambia - Zimba, Stanley; Ngalamika, Owen; Mukambo, Emmanuel; Chisha, Mike; Kayamba, Violet; Mulenga, Lloyd; Siddiqi, Omar; Saylor, Deanna; Ross, Owen A.; Atadzhanov, Masharip (Frontiers in Stroke, 2025)
BackgroundApolipoprotein E (ApoE) and monocyte chemoattractant protein-1 (MCP-1) are inflammatory markers associated with premature atherosclerosis, which leads to increased cardiovascular disease risk among people with HIV (PWH). We aimed to evaluate the association between the plasma levels of these inflammatory markers and ischemic stroke in young PWH.MethodsWe conducted a prospective case-control study at the University Teaching Hospital in Lusaka, Zambia, between March 2022 and October 2024, comparing young PWH with non-cardioembolic ischemic stroke (cases) to age- and sex-matched PWH without a history of stroke (controls). Standardized data collection instruments were used to collect information on other known risk factors for stroke, including demographic, clinical, laboratory, and imaging parameters. ELISA was done to measure ApoE and MCP-1 levels in the plasma of individuals in both the case and control groups.ResultsWe analyzed results for 50 cases and 50 controls. Compared to controls, cases were more likely to have (1) traditional stroke risk factors such as hypertension (42 vs. 2%, p = 0.001); (2) more poorly controlled HIV, including lower CD4 counts [259 (165–520) cells/μl vs. 452 (380–553) cells/μl, p = 0.030)] and higher viral loads [0 (0–4,217) copies/ml vs. 0 (0–1,578) copies/ml, p = 0.007]; (3) markers of atherosclerotic disease, including increased pulse wave velocity (PWV) [10.89 (9.99–12.15) m/s vs. 9.01 (7.989.67) m/s, p < 0.001] and carotid intima-media thickness (cIMT) [0.79 (0.70–0.99) mm vs. 0.63 (0.57–0.67) mm, p < 0.001]. Cases had lower plasma ApoE levels [1.20 (0.78–1.41) ng/ml vs. 1.55 (1.23–1.81) ng/ml, p = 0.001], but not statistically different MCP-1 plasma levels [622 (417–886) pg/ml vs. 594 (394–1,024) pg/ml, p = 0.772] compared to controls. Lower ApoE levels (aOR 0.13, 95% CI 0.03–0.68, p = 0.015), abnormal cIMT ≥0.70 mm (aOR 2.72, 95% CI 1.08–6.85, p = 0.033), and alcohol use (aOR 1,078, 95% CI 4–267,933, p = 0.013) were independently associated with ischemic stroke in multivariable analysis.ConclusionThe results suggest that lower plasma ApoE levels are independently associated with non-cardioembolic ischemic stroke in young PWH. Additional studies with larger sample sizes are needed to further explore the contribution of these inflammatory markers in young-onset HIV-associated stroke.